(untitled) (Estudos em Design, 2021)
The paper presents conceptual designs that explore the notion of ‘sustainable aesthetics’. To encourage reflective practice through form and process, and guided by sustainable principles, a practice-based (thinking-and-doing) methodology was followed by Brazilian undergraduate design students. Beginning with a theoretical overview of the historical aesthetics of chess sets (premodern, modern and contemporary) the experimental findings show different approaches to thematic chess set designs that are guided by meaning-laden cultural considerations and developed using local, natural materials or reused (disposed) industrial materials. This is the first experiment of a project that represents a creative attempt to explore and develop an aesthetic for material culture through what we have termed a ’sustainable aesthetic function’. It demonstrates how objects with the same function can be expressed in very different ways whilst all adhering to the notion of "form follows meaning’.